Thallium isotopic compositions as tracers in environmental studies: a review - Zhong, Qiaohui (2022)
Thallium is a highly poisonous heavy metal. Since Tl pollution control has been neglected worldwide until the present, countless Tl pollutants have been discharged into the environment, endangering the safety of drinking water, farmland soil, and food chain, and eventually posing a great threat to human health. However, the source, occurrence, pathway and fate of Tl in the environment remains understudied. As Tl in non-contaminated systems and from anthropogenic origin exhibits generally different isotopic signatures, which can provide fingerprint information and a novel way for tracing the anthropogenic Tl sources and understanding the environmental processes. This review summarizes: (i) the state-of-the-art development in highly-precise determination analytical method of Tl isotopic compositions, (ii) Tl isotopic fractionation induced by the low-temperature surface biogeochemical process, (iii) Tl isotopic signature of pollutants derived from anthropogenic activities and isotopic fractionation mechanism of Tl related to the high-temperature industrial activities, and (iv) application of Tl isotopic composition as a new tracer emerging tracer for source apportionment of Tl pollution. Finally, the limitations and possible future research about Tl isotopic application in environmental contamination is also proposed: (1) Tl fractionation mechanism in different environmental geochemistry processes and industrial activities should be further probed comprehensively; (2) Tl isotopes for source apportionment should be further applied in other different high Tl-contaminated scenarios (e.g., agricultural systems, water/sediment, and atmosphere).